Aeromonas hydrophila induced necrotizing fasciitis following laparoscopic cholecystectomy - Taimoor Khalid Janjua; Saba Siddique; Mohammad Faisal Ibrahim; Muhammad Nadeem Khurshaidi (Journal of the Pakistan Medical Association, 2024)
Necrotizing fasciitis [NF] is a multifaceted disease of the muscle fascia and body tissues which demands the earliest intervention. Past reviews have documented very few cases of Aeromonas Hydrophila [AH] induced NF following abdominal surgery. AH can cause fatal NF as seen in a 72 year old female patient reported at Liaquat National Hospital &Medical College; a tertiary care center in Karachi, Pakistan on 2nd April, 2022. She had a known comorbidity of hypertension and presented with the chief complaint of symptomatic gallstones for which she underwent Laparoscopic Cholecystectomy (LAPCHOL). She developed NF of the lower abdomen post-operatively. Following uneventful Laparoscopic Cholecystectomy our patient presented to the ER two days later with severe lower abdominal pain and overlying cellulitis. Fasciotomy revealed extensive myonecrosis with necrotizing soft tissue infection. —Continue